Development of Students’ Science Worksheets Based on Liveworksheet As Alternative Learning Resources for Junior High School Students - Yusro, Andista Candra; Safitri, Wulan; Ngabdiningsih, Sestu Wilujeng; Taqwim, Mohamad Ahsanul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Liveworksheet-based science student worksheets on the substance pressure topic are a form of science worksheet development and can be accessed on the Liveworksheet website. This study aims to develop science worksheets based on a "liveworksheet" on the substance pressure topic as an alternative learning resource for junior high school students. This development research uses R&D-type research with the ADDIE development model, which is modified according to the needs of researchers in the analysis, design, and development stages. The data collection techniques used in this research were observation techniques, in-depth interviews, and the profiling of students at State Junior Highschool 13 in Madiun City. The instruments used in this study were observation sheets, interview instruments, and LKPD validation sheets. The results at the analysis stage were obtained based on the findings of the researchers and the problems faced by the teachers and students, so the researchers developed a science student worksheet based on Liveworksheet on the substance pressure topic. In the design phase, the design of science student worksheets based on "liveworksheet" was carried out on the matter of substance pressure. and at the development stage, the validation results by the validator show a percentage of 91.39%.so that the product is classified in the valid category. This study's conclusion is that "liveworksheet"-based scientific student worksheets on substance pressure material are appropriate for use in the science learning process.